2013
DOI: 10.3109/10428194.2013.793323
|View full text |Cite
|
Sign up to set email alerts
|

A novel three-dimensional stromal-based model forin vitrochemotherapy sensitivity testing of leukemia cells

Abstract: The disparate responses of leukemia cells to chemotherapy in vivo, compared to in vitro, is partly related to the interactions of leukemic cells and the 3 dimensional (3D) bone marrow stromal microenvironment. We investigated the effects of chemotherapy agents on leukemic cell lines co-cultured with human bone marrow mesenchymal stem cell (hu-BM-MSC) in 3D. Comparison was made to leukemic cells treated in suspension, or grown on a hu-BM-MSC monolayer (2D conditions). We demonstrated that leukemic cells culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 31 publications
5
78
0
Order By: Relevance
“…34 Not only does this 3D system mimic the structure, it also offers the supporting microenvironment required by the leukemia cells. In this 3D system, leukemia cells are more chemo-resistant and proliferative due to this supporting niche.…”
Section: Current Applications Disease Modeling and Drug Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Not only does this 3D system mimic the structure, it also offers the supporting microenvironment required by the leukemia cells. In this 3D system, leukemia cells are more chemo-resistant and proliferative due to this supporting niche.…”
Section: Current Applications Disease Modeling and Drug Screeningmentioning
confidence: 99%
“…Hence, the limitations imposed by conventional animal models and culturing of B/BM stem cell lines in petri dishes restrict our investigations aimed at furthering the understanding of disease processes and hinder the development of high throughput drug screening protocols. 34 Recent developments including 3D printing techniques, biocompatible and biodegradable materials, together with a deeper understanding of the importance of complex dialogues between different components of B/BM, are now fueling the emergence of 3D artificial BM. A 3D BM system induced by biologically modified degradable carrier scaffolds (made of natural or synthetic biocompatible and biodegradable materials) is composed of de novo generated hematopoietic stromal cells, associated growth factors/ ECM proteins, and calcified bones.…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the major issues in designing a 3D model for chemotherapy, since the 3D model need to allow media components and cytotoxic agents to diffuse freely to target cells. An innovative 3D model was set up by Usuludin and coworkers [156]. They developed a hematopoietic coculture system using the hollow fiber bioreactor (HFBR, purchase from FiberCell Systems Inc., Federick, MD, USA).…”
Section: Co-culturing Leukemia Cell Lines and Bm Stroma Cellsmentioning
confidence: 99%
“…Previous report from Harma et al showed that specific small molecule inhibitors targeted against PI3-kinase blocked invasive cell growth more effectively in 3D than in 2D monolayer culture of prostate cancer cells [24]. Aljitawi et al compared the chemosensitivity of leukemia cells in a novel 3D stromal-based model and showed on contrary increased chemoresistance of the leukemic cells cocultured with stromal cells in non-adherent conditions [25]. Further correlations and investigation of different non-adherent models of cell proliferation will be useful for predictive testing of anti-cancer and anti-metastatic compounds.…”
Section: Discussionmentioning
confidence: 99%